Penerapan Model Pembelajaran PBL Untuk Mengembangkan Kemampuan Pemecahan Masalah Matematika - Sujana, Asep (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2015)
This research is a mixed method research with concurrent embedded strategy. The aim of theresearch is to find outthe students’ ability in mathematical problem solving that learn withproblem-based learning (PBL) is better than the conventional learning; The population of theresearchwas the mathematics education students of FKIP UNMA Banten.The sample of theresearch was two classes in semester IV. The instrumentsin this research werean essay,questionnaires and observation sheet of students’ and lecturersactivities. The data wereanalyzed quantitatively and qualitatively that was obtained from the pretest and posttest. Theresults showed thatthere is no significant difference between the students’ ability inmathematical problem solving that learnt with the problem-based learning (PBL) and theconventional learning.